Aspergillus-induced pneumonia in adult without obvious immunodeficiency: test the burst!. Issue 4 (26th April 2018) - Flament, Héloïse; Granger, Vanessa; Vezinet, Corinne; Marzaioli, Viviana; Kannengiesser, Caroline; de Chaisemartin, Luc; Hurtado-Nedelec, Margarita; Litvinova, Elena; Messika, Jonathan; Adam, Nicolas; Gougerot-Pocidalo, Marie-Anne; Dang, Pham My-Chan; et al.
Chronic granulomatous disease (CGD) is a rare primary immunodeficiency caused by a germline defect in one of the genes ( CYBB, NCF1, CYBA, NCF2 ) encoding the NADPH oxidase 2 (NOX2) components responsible for the phagocyte oxidative burst and the production of reactive oxygen species (ROS). An early diagnosis and a prompt treatment are crucial for improving outcomes in affected patients. CGD is usually diagnosed in early childhood, and more than 95% of cases are diagnosed by the age of 5 years [1, 2]. However, CGD can be diagnosed late in adulthood [1–3]. Aside from residual NOX2 activity, factors underlying late diagnosis of CGD remain poorly investigated. Here, we report a case of Aspergillus -induced pneumonia rapidly extending to fatal acute respiratory distress syndrome (ARDS) revealing a late diagnosis of CGD, which was associated with a residual mitochondria-driven neutrophil extracellular trap release (NETosis) counterbalancing the lack of functional NOX2. Written informed consent was obtained from the deceased patient's next-of-kin for publication of this case report and accompanying images. Unusual pathogen-driven sepsis should prompt to screen for chronic granulomatous disease, even in adult patients http://ow.ly/2FSi30iXUsa